Automatización del banco de calibración de manómetros para la empresa Calibration Service S.A.S. (2019)
The main objective of this project is the design of an automated system for the generation of pressure in order to calibrate pressure gauges in a range of 0 psi to 37,000 psi for the company calibration Service S.A.S The project began with the evaluation of the current system of measurement that the company has where it was defined how is the operation of the bank to then make the respective data collection and needs that the company has with the bank. Resulting in the speed and torque data required for the correct operation of the automated pressure bench, satisfying all the needs of the company. Likewise, the study was done with the necessary data to make the selection of the motors which will allow the operation and control of the coarse adjustment wheels and fine adjustment of the manometry bench, which were two gear motor with variable speed and fixed torque that It satisfies the needs of the project. Finally, the financial evaluation was carried out, which consisted in making a comparison of automated banks with the design proposed in this project.